Prevalences of Simian, Sydney and Suwon Creases and their Association with Each Other, Body Sides, Handedness, Sex and Anomalies/Diseases/Syndromes in a Population of Central India - Sharma,D. K (Sociedad Chilena de Anatomía, 2011)
The Simian and Sydney creases are variant palmar creases which have now drawn medical attention as their presence correlates strongly with numerous chromosomal anomalies and diseases. Works on these creases have been done on several human communities, racial and ethnic but no specific study is focussed out on the Indian populations. In this study 1000 Central Indian subjects (500 males and 500 females) aged between 5 to 70 years were randomly selected and examined by the authors. We found the prevalence of Simian, Sydney and Suwon creases in studied population of Central India is 14.4%, 3.6% and 2.4% respectively, which is a little higher than the figures for Asians and Caucasians claimed by earlier studies. There is no any association between these creases. The Simian crease is predominantly unilateral right side and associated with handedness. It is more common in males. The Sydney crease does not have unilateral or bilateral predominance and association with handedness but it is more common in females. The Suwon crease does not have unilateral or bilateral predominance and association with handedness but it is more common in males. There is no association of these creases with anomalies/diseases/syndromes. Conclusively this work draws attention to the importance of undertaking parallel investigations on every socio-cultural human group or population wherever possible.